2013
DOI: 10.1371/journal.pone.0056831
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Embryonic Stem Cells into Cells with Corneal Keratocyte Phenotype

Abstract: Corneal transparency depends on a unique extracellular matrix secreted by stromal keratocytes, mesenchymal cells of neural crest lineage. Derivation of keratocytes from human embryonic stem (hES) cells could elucidate the keratocyte developmental pathway and open a potential for cell-based therapy for corneal blindness. This study seeks to identify conditions inducing differentiation of pluripotent hES cells to the keratocyte lineage. Neural differentiation of hES cell line WA01(H1) was induced by co-culture w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 30 publications
(64 reference statements)
1
54
0
Order By: Relevance
“…The similar tendency was observed in human embryonic cells and corneal stromal stem [11,28]. The expressions of embryonic ocular precursor markers, PAX6 (Figure Figure 1D), which are not detected in adult stem cell or fibroblast, decreased but were still detectable after 14 d in KDM.…”
Section: Results Htmscs Differentiated Into Keratocyte Progenitor Cellssupporting
confidence: 77%
See 2 more Smart Citations
“…The similar tendency was observed in human embryonic cells and corneal stromal stem [11,28]. The expressions of embryonic ocular precursor markers, PAX6 (Figure Figure 1D), which are not detected in adult stem cell or fibroblast, decreased but were still detectable after 14 d in KDM.…”
Section: Results Htmscs Differentiated Into Keratocyte Progenitor Cellssupporting
confidence: 77%
“…The only effective therapy for corneal opacity is transplantation of corneal allografts. The transplantation of allograft has a high success rate, but still has problems, including shortage of donor corneas, and immunological rejection [11]. And CSSC derived from neural crest spontaneously differentiate into keratocyte in vivo or in vitro but stromal population of CSSC is less than 1% [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell replacement therapy using autologous or allogeneic adult limbal grafts has been the standard treatment for patients with severe limbal stem cell deficiency (LSCD) (Rama et al, 2010;Sangwan et al, 2011;Basu et al, 2016). However, in the case of bilateral epithelial defects and for the treatment of conditions affecting the stromal and endothelial cell layers, alternative stem cell sources such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been explored with a view to generating the various corneal cell types (Ahmad et al, 2007;Shalom-Feuerstein et al, 2012;Hayashi et al, 2012;Sareen et al, 2014;Mikhailova et al, 2014;Chan et al, 2013;Zhang et al, 2014;Chen et al, 2015;McCabe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…58,[137][138][139] Upregulation of AQP expression has been observed under stimuli such as dehydration in the kidney leading to overexpression of AQP2 and AQP3, [140][141][142] or hypoxia in the lung producing overexpression of AQP1 108,111,142,143 and in none of these cases have the proposals to explain AQPs overexpression been at all related to tumor proliferation. More recent studies have demonstrated involvement of AQP1 in the differentiation of stem-like cells in rat bile duct formation, 144 development of human corneal keratocytes 145 and renewal of limbal basal epithelium from a corneal epithelial stem cell niche, 146 all important roles associated with cell proliferation and differentiation. Moreover, impaired proliferation, migration and neuronal differentiation has been demonstrated in adult neural stem cells derived from AQP4 knockout mice 87 indicating a role for AQP4 in the activation and differentiation of the mice SVZ neurogenic niche.…”
Section: Apoptosis and Aqpsmentioning
confidence: 99%